2021
DOI: 10.1111/aji.13400
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage contributes to transcriptional and immunological dysregulation of testicular cells during Chlamydia infection

Abstract: Causing approximately 127 million infections globally each year, sexually transmitted Chlamydia trachomatis is a major bacterial pathogen of the human reproductive tract. 1 C. trachomatis research has primarily focussed on women, and the links between these infections and pathology, especially infertility, are relatively well established.However, the role of C. trachomatis in development of male reproductive tract disease is poorly understood. C. trachomatis-infected men have been reported as having abnormal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…The decrease in SAM levels was expected as Chlamydia highjack SAM (33). Consistent with low SAM levels, we observed that DNA was slightly hypomethylated late in infection, as previously reported (34). How can protein hypermethylation and DNA hypomethylation be reconciled?…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in SAM levels was expected as Chlamydia highjack SAM (33). Consistent with low SAM levels, we observed that DNA was slightly hypomethylated late in infection, as previously reported (34). How can protein hypermethylation and DNA hypomethylation be reconciled?…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, a study employing a murine model has postulated the direct infection of the seminiferous tubule epithelium, formed by Sertoli cells, as an interesting pathophysiological mechanism for C. trachomatis-mediated male infertility, leading to compromised spermatogenesis with reduced sperm count, motility and altered morphology of mature spermatozoa (Bryan et al, 2021).…”
Section: Human Sertoli Cellsmentioning
confidence: 99%